2009
DOI: 10.1108/09596110910930197
|View full text |Cite
|
Sign up to set email alerts
|

Wine list engineering: categorization of food and beverage outlets

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…In the foodservice industry, Tan and Lo (2008) pursued a benefit-based approach, identifying four distinct segments of patrons for a specialty coffeehouse chain. The other two restaurant-focused articles studied issues relating to the creation of wine lists Gil et al, 2009). Concerning hotels, Victorino et al (2009) demonstrated the applicability of the technology readiness index as a segmentation tool for hotel demand.…”
Section: Segmentation Targeting and Positioningmentioning
confidence: 99%
“…In the foodservice industry, Tan and Lo (2008) pursued a benefit-based approach, identifying four distinct segments of patrons for a specialty coffeehouse chain. The other two restaurant-focused articles studied issues relating to the creation of wine lists Gil et al, 2009). Concerning hotels, Victorino et al (2009) demonstrated the applicability of the technology readiness index as a segmentation tool for hotel demand.…”
Section: Segmentation Targeting and Positioningmentioning
confidence: 99%
“…Traditionally, the most common parameters for judging a restaurant's quality have been the existence of a supply of fine wines and the display of certain information such as the vintage (Berenguer et al, 2009). The wine menu is the main source of information when ordering wine during dining (Bruwer and Johnson, 2005).…”
Section: Wine Sales Management On-premisementioning
confidence: 99%
“…Sommeliers are vital to restaurants (Gil et al, 2009;Ruiz-Molina et al, 2010). Sommeliers can be either a person responsible for wine sales management (selection, purchasing and wine list creation) and serving wine at the table or a specialized waiter in charge of guiding customers through the selection of a wine for their food choice (Ruiz-Molina et al, 2010).…”
mentioning
confidence: 99%
“…Thus, by reducing risk via an information search, food-wine pairing, and recommendations could increase targeted wine sales (Wansink et al, 2006). The development of suggestive selling techniques (e.g., verbal suggestions, food-wine pairing) is also considered an important part of wine promotion (Gil, Berenguer, & Ruiz, 2009;Gue´guen, Jacob, & Boulbry, 2007;Ruiz-Molina et al, 2010;Wansink et al, 2006). For instance, Wansink et al (2006) show that food-wine pairing recommendations (e.g., the use of tent cards placed on the table) can help allay these fears.…”
Section: Introductionmentioning
confidence: 99%